Ordinance No. 10, § 5, Lamont Town Council (1910) (Lamont, Washington). - (:unkn) unknown (General Publisher, 1910)
It shall be unlawful for any person within the corporate limits of the Town of Lamont to discharge any fire arms, bomb or cannon fire cracker, or to shoot any sling shot, or to flourish or exhibit any dangerous weapon in any manner that will cause terror to the people passing, or exhibit in a rude, angry or threatening manner in a crowd of two or more persons, any pistol, bowie knife, or other dangerous weapon."
--
Keywords: DISCHARGE